Pannexin1 links lymphatic function to lipid metabolism and atherosclerosis. Issue 1 (December 2017) - Molica, Filippo; Meens, Merlijn; Dubrot, Juan; Ehrlich, Avigail; Roth, Christel; Morel, Sandrine; Pelli, Graziano; Vinet, Laurent; Braunersreuther, Vincent; Ratib, Osman; Chanson, Marc; Hugues, Stephanie; et al.
Abstract Extracellular ATP is a central signaling molecule in inflammatory responses. Pannexin1 (Panx1) channels release ATP in a controlled manner and have been implicated in various inflammatory pathologies, but their role in atherogenesis remains elusive. Using atherosclerosis-susceptible mouse models with ubiquitous deletion of Panx1 (Panx1 −/− Apoe −/− ) or with Cre recombinase-mediated deletion of Panx1 in endothelial cells and monocytes (Tie2-Cre Tg Panx1 fl/fl Apoe −/− ;Panx1 del Apoe −/− ), we identified a novel role for Panx1 in the lymphatic vasculature. Atherosclerotic lesion development in response to high-cholesterol diet was enhanced inPanx1 del Apoe −/− mice, pointing to an atheroprotective role for Panx1 in endothelial and/or monocytic cells. Unexpectedly, atherogenesis was not changed in mice with ubiquitous Panx1 deletion, butPanx1 −/− Apoe −/− mice displayed reduced body weight, serum cholesterol, triglycerides and free fatty acids, suggesting altered lipid metabolism in these Panx1-deficient mice. Mechanistically, Panx1 −/− Apoe −/− mice showed impairment of lymphatic vessel function with decreased drainage of interstitial fluids and reduced dietary fat absorption. Thus, the detrimental effect of Panx1 deletion in endothelial and/or monocytic cells during atherogenesis is counterbalanced by an opposite effect resulting from impaired lymphatic function in ubiquitous Panx1-deficient mice. Collectively, our findings unveil a pivotal role of Panx1 in linking lymphatic function to lipid metabolism and atherosclerotic plaque development.